Trends in Harmonic Analysis and Its Applications. - Christensen, Jens G. (Contemporary Mathematics., 2015)
This volume contains the proceedings of the AMS Special Session on Harmonic Analysis and Its Applications, held March 29-30, 2014, at the University of Maryland, Baltimore County, Baltimore, MD. It provides an in depth look at the many directions taken by experts in Harmonic Analysis and related areas. The papers cover topics such as frame theory, Gabor analysis, interpolation and Besov spaces on compact manifolds, Cuntz-Krieger algebras, reproducing kernel spaces, solenoids, hypergeometric shift operators and analysis on infinite dimensional groups. Expositions are by leading researchers in.